Dari Teks ke Konteks: Telaah Makro dan Mikro Asbāb al-Wurūd dalam Pemahaman Hadis - Irfani, Muhammad; Sudirman, Zulfiyani (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
Understanding hadith while neglecting the context of asbab al-wurud risks leading to rigid and misguided interpretations. Many of the Prophet’s traditions emerged within specific social conditions that require contextual interpretation. This article aims to reveal the urgency of both micro and macro asbab al-wurud in comprehending hadith texts and to present an analytical framework for uncovering their intended meanings. This study employs a qualitative approach, utilizing library research methods, with data sourced from classical hadith collections, scholarly literature, and relevant academic studies. The analysis is conducted through a descriptive-analytical approach to elaborate on the functions and models of the asbab al-wurud approach. The findings indicate that micro asbab al-wurud (direct narrations or the Prophet’s interactions) and macro asbab al-wurud (socio-historical context) play a critical role in interpreting hadith proportionally and in alignment with its intended objectives (maqashid). This study emphasizes that interpreting hadith without considering asbab al-wurud can result in distorted meanings, especially when applied to contemporary social issues.